Moral Education in M. Quraish Shihab Perspective (Analysis Study of Tafsir Al-Misbah) - Mus taqim (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Abstract: The purpose of this research is to find out the method of M. Quraish Shihab interpretation on moral verses in the tafsir (interpretation) of al- Misbah, and how is the concept of moral education according to M. Quraish Shihab in the tafsir al-Misbah. This thesis research method used literature review. Data collection techniques were through the process of organizing and selection where the data was organized and selectively managed according to the criteria based on content analysis. Then the data was managed as it is by the maudhu'i method. The mauhu'i method is a method that discusses and analyzes tasfir of moralverses, so that it becomes a unified whole. The results showed that in elaborating M. Quraish Shibah’s thoughts on moral verses, he was more likely to use the Tahlily method in interpreting the contents of the verse. His ability of high Arabic language is very visible when discussing the meaning of words in the Qur'an. This work is also rich in references, so the discussion is very broad and detailed, but still in the corridor needed by an interpretation. The components of moral education in the M. Quraish Shihab’s opinion can be summarized as follows: 1). The purpose of moral education is the achievement of the goal of human creation as the caliph of Allah in the world. 2). The learning method used in conveying moral education is a method of mental exercise, habituation, exemplary and a healthy environment. 3). The correlation between M. Quraish Shihab's moral education and Islamic education is that the substance of Islamic education that is moral education itself. Keywords: Education, Morals and Tafsir al-Misbah